The Difference of Nosocomial Urinary Tract Infection Risk Based on Chateterization Urine, Age, and Diabetes Mellitus - Sari, Edel Weisela Permata; Satyabakti, Prijono (Faculty of Public Health, 2015)
ABSTRACTNosocomial urinary tract infection is common occurs in patients with indwelling urinary chateter. Factors that caused nosocomial urinary tract infection are host, agent, and chateterization urine. The aim of this research was to analyze risk difference nosocomial urinary tract infection based on chateterization urine, age, and diabetes mellitus (DM). This study used case control with sample size 20 for each group. Case sample was patients who diagnosed urinary tract infection, while control sampel was patients who not diagnosed urinary tract infection in Haji Hospital Surabaya on 2013 until 2014. The independent variables were duration of chateterization, frequency of chateterization, age, and DM, while dependent variable was nosocomial urinary tract infection. Those variables was analyze with risk difference (RD) in Epi Info. The result showed that risk difference nosocomial urinary tract infection based on duration of chateterization is RD = 0,52 it means if changing chateter was done every seven days used, it can prevent 0,52 from 0,71 or 73,53% urinary tract infection cases, frequency of chateterization is RD = 0,43956 it means if decrease frequency of chateterization until one time used, it can prevent 0,44 from 0,79 or 55,94% urinary tract infection cases, age is RD = 0,40 it means if insertion of urine catheter as indicated and right procedure in patient with >55 old it can prevent 0,40 from 0,68 or 59,26% urinary tract infection cases, and DM is RD = 0,42 it means if preventing toward DM, it can prevent 0,42 from 0,75 or 55,56% urinary tract infection cases.Keyword: chateterization urine, age, diabetes mellitus, nosocomial urinary tract infection